High porosity microspheres with functional groups synthesized by thiol–yne click suspension polymerization. Issue 48 (18th November 2016) - Cai, Shengying; Weng, Zhulin; Zheng, Yaochen; Zhao, Bo; Gao, Zhengguo; Gao, Chao
Abstract : We employed a combination of thiol–yne click polymerization and suspension polymerization for the synthesis of porous epoxy-functionalized polymeric microspheres. Abstract : Porous polymer microspheres have been widely used in various fields, such as in ion-adsorption and drug release, and as catalyst carriers and so on. However, the facile synthesis of polymer microspheres with various available functional groups is still a challenge. Here, we firstly synthesized epoxy-functionalized porous microspheres via thiol–yne suspension polymerization of glycidyl propargyl ether and 1, 3-propanedithiol, using 1, 7-octadiyne as a crosslinker and polyethylene glycol (PEG) as a porogen. The epoxy groups on the microsphere surfaces were further modified to tert -amine, thioacetate, and carboxyl groups via thiol–epoxy click reactions. The morphologies of the porous microspheres were investigated using a scanning electron microscope (SEM). When the content of PEG was 35 wt%, porous polymer microspheres with average diameters of ∼70 μm and highest porosities of 62.45% were obtained. Subsequently, diverse modified porous microspheres were used to adsorb copper ions that were dissolved in DMF. Among these as-prepared microspheres, the thioacetate-functionalized one exhibited the highest Cu 2+ adsorption capacity (158 mg g −1 ) at room temperature. Exploration of its adsorption behaviors illustrated that the thioacetate-functionalized microspheres followed a chemically controlled monolayer adsorption mechanism. Our work presents a brand new reliable strategy for the synthesis and functionalization of non-degradable epoxy-containing porous microspheres, which can be used for the adsorption or removal of toxic metal ions (such as copper ions).